Austria : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Austria. (IMF Staff Country Reports; Country Report ;, 2018)
This 2018 Article IV Consultation highlights that Austria's economic recovery is strong and broad-based. Following several years of slow growth, Austria's output picked up markedly in 2017, and through early-2018. Output expanded by 3 percent in 2017, boosted by income tax cuts passed in 2016, higher public spending on refugees and a recovery in private investment in 2017, laying the foundation for a sustained robust expansion. Consumer and business confidence indicators have surpassed levels observed before the Global Financial Crisis and credit growth has recovered. The near-term outlook is for strong growth in 2018, at 3 percent, and a gradual return to a potential growth of about 1.75 percent over the medium-term.